2017
DOI: 10.1016/j.jweia.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic characteristics and excitation mechanisms of the galloping of an elliptical cylinder in the critical Reynolds number range

Abstract: The generation mechanisms of dry cable instabilities in the critical Reynolds number range are still unclear because of their complicated aerodynamic forces and a shortage of studies on the coupling process. Large amplitude vibrations of an elliptical cylinder in the critical Reynolds number range are reproduced in a wind tunnel, and displacements and wind pressure on the cylinder are recorded synchronously to illustrate the interactions between the cylinder motion and the aerodynamic forces in this study. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The Strouhal number of the circular cylinder used in this study agreed well with the results reported by Fox and West (1993). According to the static wind tunnel tests performed by Ma et al (2017)…”
Section: Strouhal Number (St)supporting
confidence: 89%
“…The Strouhal number of the circular cylinder used in this study agreed well with the results reported by Fox and West (1993). According to the static wind tunnel tests performed by Ma et al (2017)…”
Section: Strouhal Number (St)supporting
confidence: 89%
“…Large amplitude vibrations in the critical Reynolds number range for a smooth elliptical cylinder under normal wind have also been observed in wind tunnel tests (Ma et al, 2017b;Ma et al, 2017c). The results imply that imperfections and axial flow may not be necessary conditions for vibrations in the critical Reynolds number range.…”
Section: Introductionmentioning
confidence: 62%
“…However, the flow regime in which dry galloping occurs and the effect of surface roughness on them remains unclear. From the practical point of view, dry galloping has been observed in wind tunnel tests many times, and they have been reproduced by the author's group for circular cylinders under normal and skew winds (MA et al, 2017a;Ma et al, 2017b;Ma et al, 2017c) . However, these vibrations are rarely observed in the field.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some researchers (Bearman et al, 1987;Blevins, 1977Blevins, , 1990Fung, 1955) pay attention to the applicability of the quasi-steady assumption, and they believed that the reduced wind velocity should be higher than 10 (circular cylinders) or 30 (square cylinders). Under some specific circumstances, for example at the critical Reynolds number (Ma et al, 2017a(Ma et al, , 2017b, or for low-speed galloping (Chen et al, 2017(Chen et al, , 2021Gao and Zhu, 2017;Mannini et al, 2014Mannini et al, , 2018, the quasi-steady assumption might be disabled to modeling the galloping vibration. Another method of studying the features of galloping vibration is wind tunnel tests, which can accurately capture the galloping response without worrying about whether the quasi-steady assumption applies.…”
Section: Introductionmentioning
confidence: 99%